The use of Mediterranean native shrubs for improving the sustainability of urban environments - Leotta, Luca; Toscano, Stefania; Ferrante, Antonio; Romano, Daniela (Frontiers in Horticulture, 2025)
The Mediterranean Basin is home to one of the highest levels of biodiversity on Earth, with approximately 25,000 plant species. The typical vegetation in this region is predominantly consists of shrubs. Due to their anatomical, morphological, physiological, and biochemical characteristics, these plants can tolerate abiotic stress, particularly drought. Consequently, incorporating them could enhance the sustainability of urban green spaces. However, species native to the Mediterranean Basin are not yet widely represented in green spaces, despite their attractive ornamental traits. To quantify the contribution of Mediterranean native shrubs, a survey was conducted on Italian flora. Using a selection grid, species of potential interest were identified; these species belong to the Mediterranean chorotype and exhibit appealing ornamental characteristics. The overall attributes of these plant species support their ornamental use, owing to their form and the features of their leaves, flowers, or fruits. The investigation identified 369 species that are not currently available in commercial nurseries. The most represented families included Rosaceae, Asteraceae, Fabaceae, Lamiaceae, and Cistaceae. Although the flowering period of each species is relatively short, the blooms of different species are distributed throughout the year. Therefore, by simultaneously utilizing various species, it is possible to ensure a continuous ornamental display.